Proposta de desenvolvimento de um aplicativo de celular para aplicação do processo de enfermagem no atendimento pré-hospitalar - Valesan, Jaqueline (Universidade do Vale do Rio dos Sinos, 2017)
Nursing Assistance Systematization (SAE, acronym for the name in Portuguese) is a tool to organize nursing processes that contributes to care integrality. Health information systems are tools to optimize the care provided and contribute to the SAE applicability. OBJECTIVE: developing a mobile application prototype to register the pre-hospital care report following the Nursing process steps. METHOD: study of technological production. The prototype “PROCENF- Nursing process” was developed using SCRUM methodology and PROTO.IO® prototyping tool and followed the nursing process steps according to COFEN Resolution nr. 358/2009. The prototype evaluation was performed according to ABNT ISO/IEC 14598-6 (2004) and was adapted from Oliveira (2012), according to ISO/IEC 25010 (2011) quality requirements. A total of nineteen professionals participated of the evaluation, including ten nurses and nine IT (information technology) professionals. RESULTS: according to the nurses' evaluation, the "functional adequacy" characteristic reached 93%, "usability" with 91.6%, "performance efficiency" with 82.6%, "compatibility" with 96% and "safety" with 88%. According to the IT professionals’ evaluation, "usability" achieved 78.72%, "compatibility" with 90.2%, "Android® standards" with 83.6% and "security" with 66.6%. CONCLUSION: PROCENF prototype was considered able to become a product and it will help in the Nursing process applicability for what concerns the pre-hospital care service.
Keywords: Cuidados de enfermagem; Serviços médicos de emergência; Informática em enfermagem; Tecnologia da informação; Nursing care; Emergency medical services; Nursing informatics; Information technology; ACCNPQ::Ciências da Saúde::Enfermagem